Fosfomycin in the treatment of extended spectrum beta-lactamase-producing Enterobacteriaceae- related urinary tract infections - Ayhanim Tumturk; Senol Tonyali; Ayse Yasemin Tezer Tekce; Levent Isikay; Hakan Cime (Journal of Infection in Developing Countries)
Introduction: We aimed to demonstrate if fosfomycin tromethamine (FT) treatment could be the treatment of choice in ESBL-producing Enterobacteriaceae strains as an alternative to carbapenem particularly in patients who we would like to treat on an outpatient basis.